Case Report: Biallelic Variant in the tRNA Methyltransferase Domain of the AlkB Homolog 8 Causes Syndromic Intellectual Disability - Waqas, Ahmed; Nayab, Anam; Shaheen, Shabnam; Abbas, Safdar; Latif, Muhammad; Rafeeq, Misbahuddin M.; Al-Dhuayan, Ibtesam S.; Alqosaibi, Amany I.; Alnamshan, Mashael M.; Sain, Ziaullah M.; Habib, Alaa Hamed; Alam, Qamre; et al. (Frontiers in Genetics, 2022)
Intellectual disability (ID) has become very common and is an extremely heterogeneous disorder, where the patients face many challenges with deficits in intellectual functioning and adaptive behaviors. A single affected family revealed severe disease phenotypes such as ID, developmental delay, dysmorphic facial features, postaxial polydactyly type B, and speech impairment. DNA of a single affected individual was directly subjected to whole exome sequencing (WES), followed by Sanger sequencing. Data analysis revealed a novel biallelic missense variant (c.1511G>C; p.(Trp504Ser)) in the ALKBH8 gene, which plays a significant role in tRNA modifications. Our finding adds another variant to the growing list of ALKBH8-associated tRNA modifications causing ID and additional phenotypic manifestations. The present study depicts the key role of the genes associated with tRNA modifications, such as ALKBH8, in the development and pathophysiology of the human brain.